M. tuberculosis class II apurinic/ apyrimidinic‐endonuclease/3′‐5′ exonuclease (XthA) engages with NAD+-dependent DNA ligase A (LigA) to counter futile cleavage and ligation cycles in base excision repair. Issue 8 (30th March 2020) - Khanam, Taran; Afsar, Mohammad; Shukla, Ankita; Alam, Faiyaz; Kumar, Sanjay; Soyar, Horam; Dolma, Kunzes; , Ashish; Pasupuleti, Mukesh; Srivastava, Kishore Kumar; Ampapathi, Ravi Sankar; Ramachandran, Ravishankar
Abstract: Class-II AP-endonuclease (XthA) and NAD + -dependent DNA ligase (LigA) are involved in initial and terminal stages of bacterial DNA base excision repair (BER), respectively. XthA acts on abasic sites of damaged DNA to create nicks with 3′OH and 5′-deoxyribose phosphate (5′-dRP) moieties. Co-immunoprecipitation using mycobacterial cell-lysate, identified MtbLigA-MtbXthA complex formation. Pull-down experiments using purified wild-type, and domain-deleted MtbLigA mutants show that LigA-XthA interactions are mediated by the BRCT-domain of LigA. Small-Angle-X-ray scattering, 15 N/ 1 H-HSQC chemical shift perturbation experiments and mutational analysis identified the BRCT-domain region that interacts with a novel 104 DGQPSWSGKP113 motif on XthA for complex-formation. Isothermal-titration calorimetry experiments show that a synthetic peptide with this sequence interacts with MtbLigA and disrupts XthA–LigA interactions. In vitro assays involving DNA substrate and product analogs show that LigA can efficiently reseal 3′OH and 5′dRP DNA termini created by XthA at abasic sites. Assays and SAXS experiments performed in the presence and absence of DNA, show that XthA inhibits LigA by specifically engaging with the latter's BRCT-domain to prevent it from encircling substrate DNA. Overall, the study suggests a coordinating function for XthA whereby it engages initially with LigA to prevent the undesirable consequences of futile cleavage and ligation cycles that might derail bacterial BER.